Strategic Planning for the Micro Business Sector in Poso Regency based on SWOT Analysis - Irma Mbae; Ni Kadek Sriwati; Timotius Garatu; Tabita Rosmin Matana (ProBisnis : Jurnal Manajemen, 2023)
Business actors in running their business need an effective and efficient business strategy. In addition to gaining a competitive advantage, good strategic planning will be able to produce the right strategy to achieve the main business objectives. The MSME business is the main sector that the Indonesian economy supports and needs support and attention in its management so that the existing business cycle can be maintained and continues to run because of its very important role. This study aims to design a business strategy for micro-enterprises in Poso Naya Bakery using the SWOT Analysis approach. Data was collected using observation methods, structured interviews, and documentation. MSMEs need to do an analysis strength, weaknesses, opportunities, and threats (SWOT) of their business activities so that these MSMEs can find out about their business developments and evaluate them.